Games and Simulations in Hospitality Education: A Systematic Literature Review - Koelling, Lana; Barreda, Albert A; Kageyama, Yoshimasa; Cobos, Liza M (Journal of Tourism Management Research, 2020)
Hospitality education and training provide up to date knowledge which conveys industry objectives, history, processes, laws, and/or policies to students and employees. A new focus on the application of simulation in the hospitality industry as a means for education and training has been met with successful findings. This research studied the last three years of academic research and investigated the application of simulation in hospitality education and training. A literature search was completed in google scholar of simulation in hospitality education and training within the last three years. This review of the literature reveals that universities and hospitality organizations are actively implementing simulations as a means for education and training. Results include reduced costs, time saved, and increase in motivation and interest among students and employees when implemented effectively. The literature review provides a basis of research for instructors and managers on which to make decisions regarding education and training methods and models. However, such research is limited due to lack of consistency among learner assessments used to determine the effectiveness of simulation and the interpretive nature of participant perceptions.